2019
DOI: 10.1177/0363546519888894
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Morphologic Characteristics Predict Early Conversion to Arthroplasty After Isolated Hip Arthroscopy for Femoroacetabular Impingement

Abstract: Background: Hip arthroscopy in the setting of dysplasia and borderline dysplasia is controversial. Dysplasia severity is most often defined by the lateral center edge angle (LCEA) but can also be evaluated radiographically by the acetabular inclination (AI). Purpose/Hypothesis: The purpose was to determine the effect of AI on outcomes after isolated hip arthroscopy for femoroacetabular impingement (FAI). We hypothesized that patients with dysplasia would have higher rates of arthroplasty as well as inferior cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 49 publications
1
39
2
Order By: Relevance
“…Additional factors previously associated with conversion have been worsening preoperative evidence of arthritic changes or chondral damage 20 , 22 , 23 , 25 , 26 , 28 , 33 , 34 , 35 or acetabular morphology. 36 Contralateral THA has also been associated with increased conversion to THA after hip arthroscopy. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Additional factors previously associated with conversion have been worsening preoperative evidence of arthritic changes or chondral damage 20 , 22 , 23 , 25 , 26 , 28 , 33 , 34 , 35 or acetabular morphology. 36 Contralateral THA has also been associated with increased conversion to THA after hip arthroscopy. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Dysplasia is a complex tridimensional structural pathology, and isolated assessment based only on LCEA may be an oversimplification. 17,39 Specifically, studies in the literature have demonstrated that other radiographic metrics, such as the anterior wall index, posterior wall index, and femoral epiphyseal acetabular roof index, may be useful in the classification of dysplastic cases. 39 However, this information was not available for the included patients.…”
Section: Discussionmentioning
confidence: 99%
“…22,38 When arthroscopic management is used for this population, variables such as acetabular inclination, Tönnis grade for osteoarthritis, generalized ligamentous laxity, excessive femoral anteversion, and ligamentum teres tears have been established as potential risk factors for failure or conversion to total hip arthroplasty (THA). 17,22,34 Although a reasonable amount of data is currently available for patient-reported outcomes (PROs) for borderline dysplasia after primary arthroscopic surgery, 10 there has been a paucity of literature for this population in regard to PROs after revision hip arthroscopy.…”
mentioning
confidence: 99%
“…in current literature. A recent study by Giordano et al13 noted increasing age, decreasing LCEA, and femoral Outerbridge grades higher than 2 to be the strongest predictors of conversion to THA. Similarly, Menge et al28 demonstrated higher rates of conversion to THA in older patients, as well as nearly 90% conversion in patients with \2 mm of joint space preoperatively.…”
mentioning
confidence: 98%